Implementation of WiMAX (IEEE802.16.d) OFDM Baseband Transceiver-Based Multiwavelet OFDM on a Multi-Core Software-Defined Radio Platform. (28th March 2011) - Aboud kadhim, Mohammed; Ismail, Widad
Abstract : This paper investigates a new approach to the adaptation of the WiMAX IEEE802.16d baseband, the physical layer performance of wireless communications systems based on OFDM multiwavelet transform, using half values of coding rates, 16-QAM, and DMWT-OFDM by being applied to the SFF SDR development platform. In the new structure of WiMAX IEEE802.16d baseband, is reduce further the level of interference, and spectral efficiency is increased. The proposed design was model tested, and its performance was found to comply with International Telecommunications Union channel (ITU) models that have been elected for the wireless channel in the simulation process. The simulation approved the proposed design which achieved much lower bit error rates, increased signal-to-noise power ratio (SNR), robustness for multipath channels and does not require cyclically prefixed guard interval and have higher spectral efficiency than OFDM based on DWT and FFT also can be used as an alternative conventional OFDM in WiMAX IEEE802.16d baseband.